Publisher Correction: The influence of liposomal quercetin on liver damage induced by microwave ablation. Issue 1 (December 2017) - Duan, Xuhua; Chen, Pengfei; Han, Xinwei; Ren, Jianzhuang; Wang, Zhaoyang; Zhao, Guorui; Li, Hao
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.